2004
DOI: 10.1074/jbc.m313180200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Conserved Histidines and Arginines in the 49-kDa Subunit of Mitochondrial Complex I

Abstract: We have studied the ubiquinone-reducing catalytic core of NADH:ubiquinone oxidoreductase (complex I) from Yarrowia lipolytica by a series of point mutations replacing conserved histidines and arginines in the 49-kDa subunit. Our results show that histidine 226 and arginine 141 probably do not ligate iron-sulfur cluster N2 but that exchanging these residues specifically influences the properties of this redox center. Histidines 91 and 95 were found to be essential for ubiquinone reductase activity of complex I.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 25 publications
1
67
2
Order By: Relevance
“…The low activity of the mutant does not, however, allow us to establish the pumping stoichiometry, which may be lower than in the wild-type enzyme. Substantial inhibition of the oxidoreduction activity has also been observed by mutation of His-38 into alanine (26,27). All these findings suggest that the His-Asp motif is central for the protoncoupled electron transfer function of complex I.…”
Section: Resultsmentioning
confidence: 48%
“…The low activity of the mutant does not, however, allow us to establish the pumping stoichiometry, which may be lower than in the wild-type enzyme. Substantial inhibition of the oxidoreduction activity has also been observed by mutation of His-38 into alanine (26,27). All these findings suggest that the His-Asp motif is central for the protoncoupled electron transfer function of complex I.…”
Section: Resultsmentioning
confidence: 48%
“…We have shown previously that the mutation of histidine 226 in the 49-kDa subunit to methionine has little effect on steady-state activity and inhibitor sensitivity of complex I (20). However, when we determined the redox midpoint potential of complex I from mutant H226M at pH 7, we found that it was shifted to the negative from Ϫ140 mV to Ϫ220 mV ( Fig.…”
Section: His 226 Is the Redox-bohr Group Associated With Iron-sulfur mentioning
confidence: 93%
“…In earlier studies, we had changed this histidine to alanine, glutamine, or cysteine. These mutations also had only moderate effects on the catalytic activity of complex I, but the EPR signal of iron-sulfur cluster N2 was markedly reduced (16,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex I from both mutant and wild-type was affinitypurified from isolated mitochondrial membranes that were solubilized with n-dodecyl-␤-D-maltoside essentially as described previously (29). Construction of the mutant and its characterization have been reported elsewhere (30). Protein concentrations were determined according to a modified Lowry protocol (32).…”
Section: Methodsmentioning
confidence: 99%